Different Tillage Options and Residue Management for Improvingcrop Productivity and Soil Fertility in Wheat-Maize-Rice Cropping Pattern - Hossain, MI; Hossain, MI; Ohab, MA; Sheikh, MHR; Nag, BL (Bangladesh Agronomy Journal, 2020)
A three yearsfield experiment was conducted at Regional Wheat Research Centre, Shyampur, Rajshahiduring 2014-15 to 2017-18 with an objective to observe the effects on soil fertility and performance of the crops under different tillage and residue management for rice-wheat (RW) systems by adding a third pre-rice crop of maize. The experiment was conducted in split plot design with three replication. The tillage options viz. (i) Strip tillage (ST) (ii) Permanent bed (PB) and (iii) conventional (CT) tillage; two crop residue management, viz. (i) 0%=no residue and (ii) 30% residue retention were studied. The results indicated that keeping 30% crop residue in the field with minimum disturbance of soil had significant contribution on grain yield of wheat-maize-rice sequence compare to conventional practice of well-till without crop residue retention.The permanent bed planting system gave the highest yields of wheat (4.37 tha-1), maize (7.31 tha-1) and rice (4.40 tha-1) and followed by strip tillage and lowest in conventional tillage. Among the residue management, 30% residue retention showed the highest yields of wheat (4.46tha- 1), maize (7.39 tha-1) and rice (4.69 tha-1). Considering economic performance of all tillage systems, the permanent bed planting system performed the best among all other tillage options and followed by strip tillage. Contrarily, 30% residue retention gave the highest yield and increased 0.12-0.14% organic matter into the soil with more productive.The results indicates that, both tillage systems coupled with 30% residue retention might be a good option for higher yield as well as soil fertility for Wheat-Maize- Taman rice cropping pattern in drought prone areas of Bangladesh. Bangladesh Agron. J. 2019, 22(2): 55-66